Meraih Sukses Ala Sufi: Pendidikan Zuhud dalam Konteks Kekinian - Bunyamin, Bunyamin (Dinamika Ilmu, 2013)
Term of zuhud (ascetisme) is often misunderstood although this term came earlier than tasawuf. Experts of tasawuf have something in common to consider zuhud as the requirement should be fulfilled by everyone who approach themselves to Allah SWT whether or not they want to be blessed or loved by Allah. As long as the attentions of people just focus on the world, and as long as they love something else beside Allah, it is going to be a great obstacle to achive success in sufiâs perspective. Actually withoutapproaching ourselves to Allah, there will be no obstacle for blessing of Allah comes to his creatures, but for sufi, unlimited blessing from Allah makes them always be aware to ensure that they do not forget the one who give the blessing (Allah). Whether or not they have, happy, like, and in good occupation, there will not be any changes related to their attitude and manner to Allah SWT. Their souls keep calm because they alwaysdo zikir to Allah. They also willing to accept any decision from Allah and their attitude and behavior always refer to what Rasulullah SAW did as the example. Their ambition is they want to be safe and success both in the world and the day after (akhirat) and it is the genuine success and happiness for them.